IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE IN IMPROVING COMPANY PERFORMANCE - Astutik, Dwi; Aditya, Galuh; Kusuma, Septian Yudha; Sudarman, Sudarman; Maishanu, Umar Aliyu (Accounting Profession Journal (APAJI), 2024)
Objective: To examine the influence directly and through moderation by the independent board of commissioners between institutional and managerial ownership on company performance. Originality: Adding an independent board of commissioners as a moderator based on agency theory, which, from previous studies, is an independent variable. Method: The research uses a quantitative empirical approach, with a population of 70 companies listed in JII70 for 2021-2023; based on purposive sampling, 129 data were studied. The analysis technique uses moderated regression analysis. Results: Institutional and managerial ownership directly impact company performance to achieve ROA, which aligns with agency theory. The new finding from this test is that an independent board of commissioners strengthens this influence. Future Research Agenda: Adding a conceptual framework with an independent board of commissioners as moderation and criteria for sample companies that have an independent board of commissioners in balance with the total board in the company.